Vulnerability of the squatter communities to flood problems in Kuala Lumpur - Zahari, Rustam Khairi (Common Ground, 2008)

(untitled)
This paper discusses the contemporary academic debates in the fields of social vulnerability, social capital and adaptation, and hazard management with a focus on flood risk management in squatter settlements in Kuala Lumpur, Malaysia. These are some of the key issues for the city of Kuala Lumpur as the management of urban environment in Malaysia must be able to guarantee not only good development and planning practice but also needs to ensure that the necessary precautions and disaster strategies are in place for any eventualities. The paper attempts to highlight the affected communities’ vulnerability to environmental hazards, flood risk communication and management, all of which represent critical urban management issues in the rapidly expanding city. Respondents participating in this study include several lowincome squatter communities in Kuala Lumpur, officials from government agencies involved in flood risk management as well as community leaders and politicians. The study examines how the affected communities perceive their vulnerability and their responses in addressing these risks, and investigates the strategies adopted by the government agencies in addressing flood issues as well as in dealing with the victims of the recurring floodings.